Micro Bros. a goal-searching Cooperating Mobot System (CMS) - Ocampo, Paula Kae G. (2007)
This project aims to develop a goal-searching Cooperating Mobot System (CMS). The mobots' main task is to reach their respective goals. Being in a CMS, the mobots will cooperate with each other in achieving the task, as well as to build a two-dimensional (2D) indoor map of a certain area. The robots in themselves are autonomous, having an incorporated wall-following algorithm. The changes in the decisions in the system will be centralized, and a computer will serve as a global mapper. The global mapper will be instructing a mobot with its movements when a mobot reached an explored path. The mobots will be linked to a computer through RF Communication. The mapping software will be able to accept and plot data from two mobile robots, and will be using a Zilog ZS Encore! Microcontroller to gather data from the environment using a photo reflective sensor system. The implementation of the mobots will be enhancements of the current micro-mouse mobots in the laboratory.
Thesis (B.S. CoE)--University of the Philippines Diliman.
Keywords: Mobile robots; Mobile robots -- Design and construction; Autonomous robots -- Programming; Mobot system; Cooperating Mobot System (CMS).